2012
DOI: 10.1097/aap.0b013e31826af511
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Dimensional Ultrasound Study of Local Anesthetic Spread During Lateral Popliteal Nerve Block

Abstract: Placement of the needle tip beneath the complex fascial sheath of the sciatic nerve resulted in significantly greater perineural local anesthetic volume following a single-injection lateral popliteal approach at the nerve bifurcation and was associated with greater sensory blockade and a characteristic laminar LA spread pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 13 publications
3
52
0
1
Order By: Relevance
“…Injection under paraneurium allows better diffusion with a greater length of nerve in contact with local anesthetic. The blocks were more effective and had greater success rate than blocks performed outside of the paraneurium layer [14]. In both studies, the authors have shown that it is not an intraneural injection; indeed, no diffusion beyond the epineurium was observed.…”
Section: Subgluteal and Popliteal Approachmentioning
confidence: 96%
“…Injection under paraneurium allows better diffusion with a greater length of nerve in contact with local anesthetic. The blocks were more effective and had greater success rate than blocks performed outside of the paraneurium layer [14]. In both studies, the authors have shown that it is not an intraneural injection; indeed, no diffusion beyond the epineurium was observed.…”
Section: Subgluteal and Popliteal Approachmentioning
confidence: 96%
“…In an attempt to determine the significance of circumferential local anesthetic spread for nerve block success rate, Marhofer et al Laminar spread pattern is observed after subfascial injection versus a nonlaminar spread pattern after extrafascial injection [5]. The acquired paravertebral volume has been rendered such that the sagittal anatomy is being visualized from the lateral (intercostal space) side.…”
Section: Clinical Use Of 3-d Ultrasound For Peripheral Nerve Blockadementioning
confidence: 98%
“…Missair et al [5] published the first randomized clinical trial regarding the use of 3-D ultrasound in 2012. Patients were randomized to either receive a subfascial or extrafascial injection during lateral popliteal sciatic nerve block.…”
Section: Clinical Use Of 3-d Ultrasound For Peripheral Nerve Blockadementioning
confidence: 98%
See 1 more Smart Citation
“…intraneuralna -ne preporučuje se i trebalo bi da se izbegava, pogotovo kod blokova perifernih nerava koji su proksimalni, tačnije koji imaju malu količinu vezivnog vlakna i kod kojih na ovaj način nastaje lezija 2. intrapleksus (sub-perineuralna) je tehnika izbora kod poplitealnog bloka. Kada je u pitanju brahijalni pleksus, ova tehnika može da bude ili perineuralna (kada se okružuje svaki pojedinačni nerv) ili perivaskularna (lokalni anestetik se daje u omotač oko arterije) 3. peri-pleksus (ekstrafascijalna) -podrazumeva davanje anestetika van pleksusa, a kada je u pitanju interskalenski blok to bi značilo između skalenskih mišića [17][18][19][20][21][22][23][24][25][26] .…”
unclassified